Image-based flow analysis and fluid structure simulation using 3D computational models of myocardial infarction patients / Chan Bee Ting - Chan , Bee Ting (2018)
Myocardial infarction (MI), or commonly known as heart attack, leads to high mortality and morbidity worldwide. Early detection of MI improves treatment strategy and increases patient’s survival. Intraventricular blood flow dynamics has an incremental value in the evaluation of heart disease at an early stage because it changes accordingly in response to structural changes of the heart. Maladaptive intraventricular blood flow dynamics and excessive flow energetics were speculated as compensatory mechanisms to preserve ventricular function at the early stage of heart disease. However, several contradictory findings remain unexplained; the correlations between MI parameters and intraventricular flow variables were not quantitatively evaluated. This project aims to identify potential flow indicators and investigate the impact of MI characteristics on LV dysfunction in MI patients. To achieve this aim, phase contrast magnetic resonance (PC-MR) images of thirty MI patients and twenty healthy volunteers were analysed. A consistent measurement method for flow propagation velocity (Vp) has been proposed to overcome the influences of different LV sizes and inflow jet directions. In image-based flow analysis, intraventricular flow variables including Vp, vortex parameters and flow energetic indices were evaluated. Among them, the vortex kinetic energy (KE) could potentially indicate LV dysfunction in MI patients. Generic 3D fluid-structure interaction models were developed to investigate the relationships between MI parameters and intraventricular flow related variables. The model analysis showed that strong flow acceleration, left ventricular mechanical dyssynchrony, and vortex-infarct interaction are predominant factors leading to excessive flow energy dissipation in MI. The high systolic KE flow fluctuation index (E’) reflects energetic flow acceleration while low diastolic E’ represents efficient diastolic filling flow. The correlation between systolic and diastolic E’ indicates LV systolic-diastolic coupling mechanism.